Impact of Microbial Enzymes on Growth Performance, Micronutrient Digestibility, Tissue Protein Contents and Endogenous Enzyme Activities of Broiler Chickens Fed on Vegetable Protein Diets - Hossain, M.A.; Islam, A.F.; Iji , P.A. (International Journal of Poultry Science, 2014)
A study was conducted to investigate the effects of dietary protein sources and microbial enzyme supplementation on amino acid and mineral digestibility, tissue protein contents and endogenous enzyme activities of broiler chickens. Ross 308 day-old male broiler chicks (n = 160) were assigned randomly to four dietary treatments, each replicated five times, eight chicks per replicate, in a 2 x 2 factorial design. Two basal diets were formulated with soybean (SBM) and canola (CM) meals at a ratio of 75:25, respectively, along with basal grains and fed to the birds as such or supplemented with enzymes from 1 to 35 days. Enzymes had a positive effect on the gross responses (feed intake, body weight and feed conversion ratio) of the broiler chickens at 35 days. However, feed intake was significantly different (p<0.001) between protein sources but this did not affect (p>0.05) body weight and feed conversion ratio (FCR) between 1 and 35 days. Tissue protein contents and endogenous enzyme activities at 21 days (except for maltase) were unaffected by dietary sources and microbial enzyme supplementation. The activity of maltase was higher (p<0.05) on CM diets than on SBM diets, but this effect was absent when diets were supplemented with enzymes. The digestibility of threonine and lysine, measured at 35 days, was significantly (p<0.01) higher on SBM diets than on CM diets. Similarly the digestibility of valine, isoleucine and leucine was also higher (p<0.05) on SBM diet than in CM diet. Addition of enzymes also significantly (p<0.05) increased the digestibility of histidine, threonine, lysine and isoleucine, but not the digestibility of other amino acids measured at this period (35d). Enzymes had no effect (p>0.05) on mineral digestibility of broilers over the test period. The digestibility of Cu, Zn and Mg was increased (p<0.05) on CM diet, whereas Ca digestibility was higher on SBM diet at 35 days. It can be concluded that the improved growth of the birds might be a result of increased digestibility of amino acids and increase in feed consumption.